Second-Best Congestion Pricing in General Static Transportation Networks with Elastic Demand - Erik T. Verhoef (Tinbergen Institute, 1998)
This paper studies the second-best problem where not all links of acongested transportation network can be tolled. The second-best taxrule for this problem is derived for general static networks, so thatthe solution presented is valid for any graph of the network, and forany set of tolling points available on that network. It isdemonstrated that the solution obtained indeed generalizes a numberof known second-best tax rules presented earlier in the literature,for specific cases of the general problem discussed in the presentpaper. Finally, it is demonstrated that, for instance by using theconcept of 'virtual links', the analysis can be applied rather easilyalso to a broader class of second-best problems in static networks.
Keywords: 330; Verkehrsweg; Verkehrsinfrastruktur; Bottleneck; Straßenbenutzungsgebühr; Lastmanagement; Theorie